Research on simulated devices for Solar photovoltaic grid-connected generation system - quan-zhu Zhang; yan-xiang Ge; yong-hong Deng (MATEC Web of Conferences, 2017)
On the standpoint of energy conservation and emission reduction, one device simulated photovoltaic grid-connected generation system based on SPWM was designed in the paper. And DC/AC inverter could transduce efficiently direct current to alternating current. The MCU(Micro-Control-Unit), in this system could achieve the control method for maximum-power-point and tracking for frequency and phase. Moreover, the MCU could implement PWM (Plus-Width Modulating) through programming. The system showed clearly the whole photovoltaic grid-connected generation system using simulated methods and ways.